69 PATTERNS OF LOCAL/REGIONAL FAILURE AFTER HIGH DOSE RADIATION IN PATIENTS WITH INOPERABLE/UNRESECTABLE NON-SMALL CELL LUNG CANCER. (1st March 2005) - Kong, F. M.; Cronin, P.; Chetty, I.; Tatro, D.; Hayman, J. A.; Haken, Ten R.
Abstract : Purpose: To study the pattern of local failure for patients of non-small cell lung cancer (NSCLC) treated on a conformal therapy dose escalation protocol. Materials/Methods: Subjects included patients who had failed locally and a matched group without failures after 3-D conformal radiation per a phase I dose escalation trial. Radiation doses were computed using an equivalent path length algorithm, ranged from 65.1 to 102.9 Gy in 2.1 Gy fractions. The original and recurrent gross target volume (GTV and RGTVs) were contoured by a radiologist and a radiation oncologist. The original and planning target volume (PTVs and RPTVs) were from GTVs plus 1-1.5 cm expansion. DVHs of each structure were constructed and generalized equivalent uniform doses (EUD = Σi (di)a1/a) were also computed. Marginal failure was defined for RGTVs covered by the original 10% to 90% isodose surfaces, while central failures were inside the original 90-100% isodose surfaces. Results: There are no significant differences between the failed and controlled groups with regard to average original GTV volumes, average total prescription doses, mean GTV doses, or mean PTV doses, and minimal PTV doses. Of the 15 RGTVs, five are located across the margins of the original PTVs, nine mostly within the PTVs, and one outside of the original PTVs. The average EUDs for the RGTVs and RPTVs are 60 ± 30 and 49 ± 31 Gy, respectively, significantly below the prescribed doses (p = 0.03). Forty percent RGTVs and 60% RPTVs had EUDs less than 66 Gy (a common prescription dose). The RGTVs are not encompassed by the original 90% isodose surfaces for 7 of the 15 cases, all of which failed at the margins of or outside the original PTVs. The EUDs for these seven RGTVs are much less than (1%-63% of) the EUDs for the original PTVs. When the doses are recalculated using the Monte Carlo algorithm, additional 10-20% dose reductions are found for patients who failed after high dose radiation. Conclusions: Inadequate dose, marginal miss and under-dose from inaccurate calculation algorithm all contributed to the local failure after 3-D conformal radiation therapy. In addition to dose escalation, further clinical trials should focus on margin definition and accurate dose calculation to improve the tumor control in NSCLC.